2012
DOI: 10.1287/orsc.1100.0643
|View full text |Cite
|
Sign up to set email alerts
|

Status Differences in the Cognitive Activation of Social Networks

Abstract: We develop a dynamic cognitive model of network activation and show that people at different status levels spontaneously activate, or call to mind, different subsections of their networks when faced with job threat. Using a multimethod approach (General Social Survey data and a laboratory experiment), we find that, under conditions of job threat, people with low status exhibit a winnowing response (i.e., activating smaller and tighter subsections of their networks), whereas people with high status exhibit a wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
193
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(207 citation statements)
references
References 75 publications
13
193
0
1
Order By: Relevance
“…Over the past few years, scholars have demonstrated that cognitively informed network theories can significantly deepen our comprehension of both the effects and processes occurring through interpersonal networks. Prior studies found that individual cognition affects people's mental representation of the network (Simpson et al, 2011), which parts of the network they activate (Smith, Menon & Thompson, 2012), and which contacts they turn to (Elliott, Haney & Sams-Abiodun, 2010). Our results complement the work by DeRue, Nahrgang, and Ashford (2015) in elucidating the socio-cognitive underpinnings of emergent leadership structures in informal groups.…”
Section: Contributionssupporting
confidence: 81%
“…Over the past few years, scholars have demonstrated that cognitively informed network theories can significantly deepen our comprehension of both the effects and processes occurring through interpersonal networks. Prior studies found that individual cognition affects people's mental representation of the network (Simpson et al, 2011), which parts of the network they activate (Smith, Menon & Thompson, 2012), and which contacts they turn to (Elliott, Haney & Sams-Abiodun, 2010). Our results complement the work by DeRue, Nahrgang, and Ashford (2015) in elucidating the socio-cognitive underpinnings of emergent leadership structures in informal groups.…”
Section: Contributionssupporting
confidence: 81%
“…The engagement of the rooted coordinator with diverse cultural others can also affect his or her "absorptive capacity," which can help to sort higher-quality knowledge from lower quality, as well as manage the information-overload challenges associated with bridging structural holes (Haas, 2006). Furthermore, information advantages associated with a high level of engagement can also partially offset the effects of the relational and cognitive constraints associated with a high level of cultural embeddedness, namely habitual reliance on information sources that are culturally or physically proximal or whose knowledge and expertise are well known to the broker (Borgatti & Cross, 2003;Smith, Menon, & Thompson, 2012). Therefore, the rooted coordinator is particularly effective when bridging complex culture holes and facilitating collaborations that requires in-depth understanding and engagement not only with one's own cultural group, but also with the culturally diverse global party.…”
Section: Rooted Operatormentioning
confidence: 99%
“…Networks could open up structurally, with actors tapping acquaintances who are most likely to provide novel information and diverse perspectives on problem-solving [21]. Experiments show that persons facing threatening job changes, for example, disproportionately turn to their weak ties and reduced their triadic closure [22,23], broadening their options and access to novel job information [24]. Conversely, external shocks could be associated with networks "turtling up," with actors relying on well-worn sources of information, network insiders, and highly clustered relationships [25,26] that promote trustworthiness but narrow social cognition [22,24,25,27].…”
Section: Introductionmentioning
confidence: 99%